PENGARUH MEDIA IKLAN TERHADAP KEMAMPUAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP NEGERI 47 PALEMBANG - Meinanda Saputri (Seminar Bahasa dan Sastra Indonesia, 2019)
This research aims to determine the effect of advertising media on the ability to write persuasion text in eightth grade students SMP Negeri 47 Palembang. The research method used in this study is a quasi-experimental method. Sample selection is done randomly, and the sample chosen in this study consisted of two classes namely class VIII.5 which amounted to 27 students as the control class that received treatment using poster media and class VIII.6 which amounted to 27 students as the experimental class that received treatment using advertising media. The data collection technique in this study used test technique and data processing technique used the t-test with SPSS 24 program. The results showed that there were differences in test results between the experimental class and the control class. The experimental class gets the initial test average value 43,15 and the control class obtained the final test grade average score of 40,37. While the average value of the experimental class final test 74,63 and the average value of the final class of the control class 59,44. The data analysis with t-test indicate that t-count > t-table = 6,559 > 2,007 with df = 52 at success rate of 95% (α=0,025), meaning that there are significant differences between the two groups of sample, because t-count is greater than t-table, then Ho is rejected and Ha is accepted, meaning that the experimental class is more significant than the control class. Therefore, advertising media has an effect on the ability to write description text in eightth grade students SMP Negeri 47 Palembang. Keywords: Media, writing, persuasion text